Answer:
w = 3
Step-by-step explanation:
-6(w - 4) + 8W=6(w + 2)
-6w + 24 + 8w = 6w + 12
2w + 24 = 6w + 12
12 = 4w
3 = w
Answer:
520 because 65 x 8 is 520
Step-by-step explanation:
Answer:
a. Narrower
b. Shifts left
c. Opens up
d. Shifts up
Step-by-step explanation:
The original quadratic equation is y = x²
The given quadratic equation is y = 5·(x + 4)² + 7
The given quadratic equation is of the form, f(x) = a·(x - h)² + k
a. A quadratic equation is narrower than the standard form when the coefficient is larger than the coefficient in the original equation
The quadratic coefficient is 5 > 1 in the original, therefore, the quadratic equation is <em>narrower</em>
b. Given that the given quadratic equation has positive 'a', and 'b', and h = -4, therefore, the axis of symmetry <em>shifts left</em>
c. The quadratic coefficient is positive, (a = 5), therefore, the quadratic equation <em>opens down</em>
d. The value of 'k' gives the vertical shift, therefore, the given quadratic equation with k = 7, <em>shifts up.</em>
To make this simple
If two pairs corresponding angles in a pair of triangles are congruent then the triangles are similar
9. i dissagree because 0.70 and 0.7 is the same thing
10. is 1.45
11. is 0.37